CONSTRUCTION OF MORTALITY TABLES USING UNIFORMLY DISTRIBUTION OF DEATH AND CONSTANT FORCE BASED APPROACHES IN TMI 2019 - Nurul Tri Narlitasari; Riri Rioke; Wulan Setyani; Anisa Nurbayti; Agung Prabowo (International Journal of Quantitative Research and Modeling, 2022)
Insurance aims to protect a person from financial losses that may occur due to an unexpected event. On the determination of insurance premiums used mortality tables. However, on the mortality table contains only a round age. While an event cannot be ascertained when it occurs, it could be at the beginning of the year, in the middle, or at the end of the year. Therefore, to determine insurance premiums at an age that is not round, a mortality table that contains fractional age is needed. In this study, the mortality table used is the 2019 Indonesian Mortality Table (IMT) issued by the Indonesian Actuary Association (IAA). The methods used for determining fractional age mortality tables are the Uniform Distribution of Death (UDD) approach and the Constant Force of Mortality (CF) approach. In this study, the results of the 2019 TMI calculation were obtained for fractional ages with male and female genders using two approaches, namely the UDD and CF approaches. In both sexes, the result was obtained that the chance of death calculated using the UDD approach was smaller compared to the CF approach. The resulting graph shows that the 2019 TMI death chances with the UDD and CF approaches did not show significant differences for both men and women, so both approaches can be used to calculate the chance of death at the fractional age of TMI 2019.